2020
DOI: 10.3390/d12010027
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of a Large Collection of Natural Populations of Mango (Mangifera indica Linn.) Revealed by Agro-Morphological and Quality Traits

Abstract: Collection, characterization and utilization of genetic resources are crucial for developing varieties to meet current and future needs. Although mango is an economically important fruit tree, its genetic resources are still undocumented and are threatened in their natural habits. In this study, the variability of 452 mango accessions from three regions in China (Nujiang, Lancang river and Honghe) was assessed using 41 descriptors including qualitative and quantitative traits, with the aim to identify mango ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 42 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Indonesia and Malaysia also have several types of wild mangoes (Singh et al 2016). These wild types are vital to support mango breeding programs (Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia and Malaysia also have several types of wild mangoes (Singh et al 2016). These wild types are vital to support mango breeding programs (Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We used the FAMD technique to characterize the germplasm using quantitative and qualitative variables simultaneously and to understand which traits and phenotypes are important for classification purposes. Similar to studies in other species, the dimensionality reduction by FAMD indicated that various factors are needed to capture most of the variance [48,49]. This can be explained by considering that the dataset is complex (being made of an equal and substantial number of qualitative and quantitative variables) and that the relationships between the two types of traits are non-linear, bearing in mind the observed significant relationships between quantitative traits.…”
Section: Discussionmentioning
confidence: 60%
“…Flowering occurs from January to March, and the fruiting period is April to July. The most widely cultivated mango varieties in these areas are Keitt, Guifei, Sannian, Nang Klangwan, and JinHwang [7,[97][98][99]. Honghe, located in the dry and hot river valley (north tropical climate regions), has an average annual temperature of 24.9 °C, annual sunshine time of 2300 h, and average annual precipitation of 800-1000 mm, while Baoshan, located in west of Yunnan (south subtropical climate regions), reports an average annual air temperature of 21.5 °C, annual sunshine time of 2300 h, and average annual precipitation of 750-900 mm [99][100][101][102].…”
Section: Discussionmentioning
confidence: 99%